2022
DOI: 10.3390/biom12020309
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Wnt Pathway as a Therapeutic Target for Prostate Cancer

Abstract: Aberrant activation of the Wnt pathway is emerging as a frequent event during prostate cancer that can facilitate tumor formation, progression, and therapeutic resistance. Recent discoveries indicate that targeting the Wnt pathway to treat prostate cancer may be efficacious. However, the functional consequence of activating the Wnt pathway during the different stages of prostate cancer progression remains unclear. Preclinical work investigating the efficacy of targeting Wnt signaling for the treatment of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 255 publications
(485 reference statements)
1
16
0
Order By: Relevance
“…The altered Wnt pathway activity has been tied to malignant growth and progression in many tumor types [ 8 , 9 , 10 , 160 , 161 , 162 , 163 ]. Consistently, Wnt co-stimulation has been identified as a key driver of advanced PCA progression, with the Wnt pathway alterations being evident in 18% of the CRPC tumors [ 10 , 11 , 12 , 14 , 157 , 162 , 163 , 164 , 165 ]. Zi et al similarly detected the Wnt pathway activation in CRPC through RNA-seq and microarray analyses [ 165 ], and the KEGG pathway-enrichment analyses have highlighted the upregulation of key Wnt pathway components in PCA, following ADT exposure [ 166 ].…”
Section: Non-ar Pathwaysmentioning
confidence: 89%
See 2 more Smart Citations
“…The altered Wnt pathway activity has been tied to malignant growth and progression in many tumor types [ 8 , 9 , 10 , 160 , 161 , 162 , 163 ]. Consistently, Wnt co-stimulation has been identified as a key driver of advanced PCA progression, with the Wnt pathway alterations being evident in 18% of the CRPC tumors [ 10 , 11 , 12 , 14 , 157 , 162 , 163 , 164 , 165 ]. Zi et al similarly detected the Wnt pathway activation in CRPC through RNA-seq and microarray analyses [ 165 ], and the KEGG pathway-enrichment analyses have highlighted the upregulation of key Wnt pathway components in PCA, following ADT exposure [ 166 ].…”
Section: Non-ar Pathwaysmentioning
confidence: 89%
“…The Wnt pathway is separated into the classical Wnt/β-linked protein pathway, as well as the non-classical β-linked protein independent pathway [ 167 ]. In low-androgen settings, studies have found that AR interacts with the classical pathway, promoting the Wnt pathway activation [ 161 , 164 , 168 ]. On the one hand, a regulatory mechanism exists for Wnt and AR such that an increase or decrease in one can cause a reciprocal decrease or increase in the other.…”
Section: Non-ar Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone morphogenic protein (BMP) pathway, integral to mesenchymal stem cell differentiation, shows mixed roles in cancer, with pharmacological inhibition showing promise in certain bone metastasis models [ 187 , 188 ]. The Wnt signaling pathway, crucial in osteogenesis and cancer metastasis, offers potential therapeutic targets, including various inhibitors that are being investigated for their efficacy in prostate and breast cancers [ 189 ]. The CXCL12/CXCR4 axis, significant in bone metastasis regulation, has inhibitors in clinical trials showing potential to reduce cancer cell proliferation and migration [ 190 , 191 ].…”
Section: Managementmentioning
confidence: 99%
“…In metastatic CRPC, increased expression of nuclear β-catenin and the target genes of the Wnt/β-catenin signaling pathway have been shown. It is thought that this signaling pathway underlies the acquisition of a selective advantage by cells under the influence of therapy [ 13 , 14 ]. One promising agent for study targeting Wnt/β-catenin signaling is the tankyrase inhibitor XAV939.…”
Section: Introductionmentioning
confidence: 99%